Ancient DNA from permafrost: Beringian soil provides insights into PCR inhibition and antibiotic resistance - King, Christine E. (My University, 2011)
The manuscripts included here describe two diverse projects that developed from a metagenomic pilot study of 30,OOO-year-old Beringian permafrost. To ensure that high yields of DNA were available for deep amplicon sequencing, our initial efforts focused on measuring PCR inhibition in low copy samples. In the first study, we demonstrate how these measurements can be applied to determine optimal combinations of PCR facilitators and to evaluate the tradeoff in DNA recovery that results from sample dilution. We also discuss the methods of inhibition measurement commonly used (amplification efficiency of the samples or quantification cycle shifts of internai positive controls) and show that neither method should be used alone. The results of our metagenomic study and the rigorous procedures used to authenticate the data are presented in the second report, which focuses on our discovery of antibiotic resistance genes in the same samples; here they provide contextual evidence that the site is free of modern contaminants and anthropogenic factors, offering an ideal setting to study the evolution of resistance prior to the antibiotic era. We report a highly diverse collection of ancient DNA sequences that cluster with those found in characterized tetracycline-, vancomycin-, and penicillin-resistant bacteria, and are distinct from homologues with other functions. To verify the functionality of these genes, we focused on the vanHAX operon, which functions exclusively as a resistant determinant; not. only was the complete operon present, but with successful isolation and expression of vanA, we were also able to confirm the activity and specificity of the D-Ala-D-Lac ligase component. These results have serious implications for responsible antibiotic development and deployment, which must consider the potent ial existence of diverse resistance mechanisms in the environment.
Keywords: Biology; Biology